2020
DOI: 10.3390/f11070737
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Responses of Magnolia schiedeana Schltdl., a Relict-Endangered Mexican Cloud Forest Tree, to Climatic Events: Evidences from Leaf Venation and Wood Vessel Anatomy

Abstract: The Mexican tropical montane cloud forest trees occur under special and limited climatic conditions; many of these species are particularly more sensitive to drought stress. Hydric transport in leaf veins and wood features are influenced by climatic variations and individual intrinsic factors, which are essential processes influencing xylogenesis. We assessed the plastic response to climatic oscillation in two relict-endangered Magnolia schiedeana Schltdl. populations and associated the architecture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
2
14
0
1
Order By: Relevance
“…Although there has been a long-standing recognition of the importance of climate variation on tree-ring width variation for TMCF tree species 20 , the assessment of how drought influences vessel traits are relatively new. How climate triggers resilience in vessel traits may increase our understanding of how TMCF tree species will respond to future climate change 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been a long-standing recognition of the importance of climate variation on tree-ring width variation for TMCF tree species 20 , the assessment of how drought influences vessel traits are relatively new. How climate triggers resilience in vessel traits may increase our understanding of how TMCF tree species will respond to future climate change 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the long-standing recognition of the importance of climate variation on tree ring assessment for the TMCF tree species 43 , the drought influence assessment on vessel trait is relatively new. Climate and environmental effects on vessel traits trigger resilience species may help understand how TMCF tree species will respond to further climate change 20 . We found that T max and EvT influenced specific vessel traits (e.g., vessel diameter, vulnerability index) developing narrow vessels), hence functional adaptive in xylem properties 40 as other TMCF tree species 15 , however, a high number of narrow vessels is significantly safer in terms of embolism resilience compared to a few large vessels 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Magnolia schiedeana is a perennial tree (>200 years) up to 25 m in height (Rodríguez-Ramírez et al, 2020). The species flowers from April to June, has sexual reproduction but can reproduce clonally by sprouting from the base of the trunk (Vásquez-Morales et al, 2017).…”
Section: Study Speciesmentioning
confidence: 99%
“…The TMCF of Mexico are composed of highly heterogenous forest that can vary markedly in environmental conditions (Gual-Díaz & González-Medrano, 2014). Local environmental differences have been suggested to generate the large intraspecific morphological variations observed across populations of M. schiedeana (Vite, 2016;Rodríguez-Ramírez et al, 2020). This environmental heterogeneity may have led to differential habitats preferences and thus to divergence by ecological factors, a potential hypothesis that could be tested in the future.…”
Section: Effects Of the Pleistocene In The Phylogeographical Structure And Demographic Changesmentioning
confidence: 99%
“…Although more than half of the Earth's land is covered by non-forest vegetation [11], vessel anatomical traits of plants are largely represented by anatomical and dendrochronological studies on trees and shrubs [12][13][14][15][16][17][18][19][20][21][22][23], with relatively few similar studies on herbaceous species [11,[24][25][26][27]. Studies have shown that there are annual growth rings in the secondary root xylem of perennial herbaceous species [11,28], with wider vessels at the beginning of the growing season and narrower vessels at the end of the growing season [29].…”
Section: Introductionmentioning
confidence: 99%